The challenge of unidentified decedents in Africa: The need for training and research in forensic odontology to strengthen a multidisciplinary approach - Chandler, Susan; Sudi, Stephen M.; Bailie, Keané C.; Chetty, Manogari (Frontiers in Oral Health, 2022)
Introduction: Managing unidentified decedents suspected to be undocumented migrants is a growing humanitarian crisis. Identification of the dead and the right of the family to know the fate of a decedent is a fundamental human right. Forensic odontology methods can provide information that will assist in the identification, especially in low-resource settings. South Africa, a transit and migration destination in Africa, is facing a problem of unidentified decedents in the forensic pathology services of major metropolitan areas. Discussion: The fundamental application of forensic odontology relies on the availability of good antemortem dental records. The state of dental records was reported to be suboptimal in South Africa and other African countries. Incorporating forensic odontology into the undergraduate training in the 23 dental schools in Africa will increase the understanding of the value of maintaining accurate dental records and potentially facilitate collaboration with dentists and forensic odontologists in cases where dental features can be used for identification. South Africa offers postgraduate training in forensic odontology, and prospects for future research in Africa need to be explored. Conclusion: The development of a forensic odontology career path and research prospects will provide African countries with the potential for building multidisciplinary teams to assist in solving the challenge of unidentified decedents.